A modified high-nickel ternary positive electrode material and preparation method thereof
Modifying the high-nickel ternary cathode material through cobalt doping and coating technology solves its cycleability and thermal stability problems, significantly improves the electrochemical performance and cycle life, and is suitable for industrial production.
Patent Information
- Application Number
- CN202210312506.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-03-28
AI Technical Summary
High-nickel ternary cathode material has poor circulation, thermal stability and safety during high-temperature synthesis, storage in the air and repeated charging and discharge, resulting in the layered structure becoming a rock salt structure, inhibiting lithium ion transmission, and in the air The reaction between moisture and carbon dioxide forms poor residual lithium compounds, affecting the circulation process of lithium-ion batteries.
The high-nickel ternary cathode material is modified by cobalt doping and cobalt coating, and a uniform cladding layer is formed by spraying and microwave heating to reduce residual lithium content and improve circulation performance.
It significantly improves the circulation performance and electrochemical performance of high-nickel ternary cathode materials, solves the gas production problem during battery circulation, and is simple in preparation and low in cost, suitable for large-scale industrial production.
Smart Images

Figure HDA0003568892750000011 
Figure HDA0003568892750000012 
Figure HDA0003568892750000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a modified high-nickel ternary positive electrode material and a preparation method thereof. Background Art
[0002] The demand for high energy density in power batteries has promoted the development of high-nickel cathode materials, lithium-rich manganese-based cathode materials, and lithium-sulfur batteries. x Co y Mn 1-x-y O2 (NCM) has the advantages of high specific capacity, good rate performance and relatively low cost. It occupies an absolute leading position among various positive electrode materials and is considered to be one of the most promising positive electrode materials for power batteries.
[0003] However, high-nickel ternary cathode materials have disadvantages such as poor cyclability, thermal stability and safety. During high-temperature synthesis, storage in air and repeated charge and discharge, the layered structure of high-nickel ternary cathode materials will change to a rock salt structure. This transformation has an inhibitory effect on the transmission of lithium ions from the surface of the high-nickel ternary cathode materials to their interior. In addition, during storage in air, the high-nickel ternary cathode materials will react with moisture and carbon dioxide in the air to form residual lithium compounds containing LiOH, LiHCO3 and Li2CO3 on their surface. These residual lithium compounds will have an adverse effect on lithium-ion batteries, causing lithium-ion batteries to produce gas during the cycle process, and will also cause the slurry of high-nickel ternary cathode materials to gel during the manufacturing process of lithium-ion batteries.
[0004] Based on these problems existing in the high-nickel ternary positive electrode materials themselves, it is of great significance to develop a technology that can effectively improve or overcome the defects of the high-nickel ternary positive electrode materials themselves, which will be conducive to promoting the further development and utilization of high-nickel ternary positive electrode materials. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a modified high-nickel ternary positive electrode material and a preparation method thereof, wherein the high-nickel ternary positive electrode material is modified by cobalt doping and cobalt coating, and the cobalt doping is beneficial to improving the cycle performance of the high-nickel ternary positive electrode material, and the cobalt layer coated by microwave heating can reduce the residual lithium content in the high-nickel ternary positive electrode material, thereby effectively solving the gas production problem during the battery cycle. Moreover, this preparation method is simple, low-cost, environmentally friendly, and suitable for large-scale industrial production.
[0006] A first aspect of the present invention provides a high-nickel ternary positive electrode material, wherein the ternary positive electrode material is a high-nickel ternary positive electrode material doped with and coated with cobalt.
[0007] According to the first aspect of the present invention, in some embodiments of the present invention, the mass fraction of cobalt doped in the high-nickel ternary positive electrode material is 0.2-2%.
[0008] In some preferred embodiments of the present invention, in the high-nickel ternary positive electrode material, the thickness of the cobalt element coating layer is 20nm to 200nm.
[0009] In some preferred embodiments of the present invention, in the high-nickel ternary positive electrode material, the thickness of the cobalt element coating layer is 50nm to 100nm.
[0010] The second aspect of the present invention provides a method for preparing the high-nickel ternary positive electrode material according to the first aspect of the present invention, the preparation method comprising the following steps:
[0011] (1) Cobalt-containing compound A is coated on nickel-cobalt-manganese hydroxide precursor Ni x Co y Mn 1-x-y (OH)2, preparing a nickel-cobalt-manganese hydroxide precursor coated with cobalt element on the surface;
[0012] (2) mixing the nickel-cobalt-manganese hydroxide precursor coated with cobalt described in step (1) with a lithium-containing compound and calcining the mixture to prepare a high-nickel ternary positive electrode material doped with cobalt on the surface;
[0013] (3) The high-nickel ternary positive electrode material doped with cobalt element described in step (2) is mixed with the cobalt-containing compound B and subjected to microwave treatment to prepare a high-nickel ternary positive electrode material LiNi x Mn y Co 1-x-y O2·nLiCoO2.
[0014] According to the second aspect of the present invention, in some embodiments of the present invention, the chemical formula of the nickel-cobalt-manganese hydroxide precursor in step (1) is Ni x Co y Mn 1-x-y In (OH)2, 1.00>x≥0.6, y>0, 1-xy>0.
[0015] In some preferred embodiments of the present invention, the nickel-cobalt-manganese hydroxide precursor Ni in step (1) x Co y Mn 1-x-y (OH)2 is Ni 0.95 Co 0.03 Mn 0.02 (OH)2.
[0016] In some preferred embodiments of the present invention, the Ni 0.95 Co 0.03 Mn 0.02 (OH)2 was purchased from Guangdong Brunp Recycling Technology Co., Ltd.
[0017] In some preferred embodiments of the present invention, the chemical formula of the high nickel ternary positive electrode material doped with cobalt element in step (3) is LiNi x Mn y Co 1-x-y In O2·nLiCoO2, 1.00>x≥0.6, y>0, 1-xy>0, n>0.
[0018] Among them, LiCoO2 exists in the form of doping and coating on LiNi x Mn y Co 1-x-y In O2.
[0019] In some preferred embodiments of the present invention, the specific steps in step (1) are to place the solution formed by dissolving the cobalt-containing compound A in water in a spray device for standby use; x Co y Mn 1-x-y (OH)2 is placed in a mixing device with a heating function and stirred. During the stirring process, the cobalt-containing compound A is coated on the Ni by a spray method. x Co y Mn 1-x-y (OH)2 surface, and a nickel-cobalt-manganese hydroxide precursor coated with cobalt element was prepared.
[0020] In some preferred embodiments of the present invention, the nickel cobalt manganese hydroxide precursor Ni x Co y Mn 1-x-y The stirring speed of (OH)2 is 200-800rpm.
[0021] In some preferred embodiments of the present invention, after the spraying is completed, Ni x Co y Mn 1-x-y (OH)2 continues to stir.
[0022] In some more preferred embodiments of the present invention, the stirring time after spraying is continued for 30-300 minutes.
[0023] In some more preferred embodiments of the present invention, the spraying time of the spraying method is 5 to 120 minutes.
[0024] In some more preferred embodiments of the present invention, the spraying time of the spraying method is 20 to 100 minutes.
[0025] In some more preferred embodiments of the present invention, the spraying time of the spraying method is 30 to 60 minutes.
[0026] In some more preferred embodiments of the present invention, the spray flow rate of the spray method is 3 to 6 mL / min.
[0027] In some more preferred embodiments of the present invention, the mass ratio of the cobalt-containing compound A to water is 1:(1-100).
[0028] In some preferred embodiments of the present invention, the cobalt-containing compound A in step (1) comprises at least one of cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, and cobalt sulfate heptahydrate.
[0029] In some preferred embodiments of the present invention, the Ni x Co y Mn 1-x-y The molar ratio of (OH)2 to the cobalt element in the cobalt-containing compound A is 1:(0.002-0.02).
[0030] In some preferred embodiments of the present invention, the lithium-containing compound in step (2) includes at least one of lithium hydroxide, lithium carbonate, lithium fluoride, lithium chloride, and lithium nitrate.
[0031] In some preferred embodiments of the present invention, the Ni x Co y Mn 1-x-y The molar ratio of (OH)2 to the lithium element in the lithium-containing compound is 1:(1-1.2).
[0032] In some preferred embodiments of the present invention, the calcination temperature in step (2) is 700-1000°C.
[0033] In some preferred embodiments of the present invention, the calcination time in step (2) is 10 to 20 hours.
[0034] In some preferred embodiments of the present invention, the cobalt-containing compound B in step (3) includes at least one of cobalt oxide, cobalt tetroxide, cobalt oxyhydroxide, cobalt hydroxide, cobalt trioxide, cobalt carbonate, cobalt acetate, and cobalt oxalate.
[0035] In some preferred embodiments of the present invention, the molar ratio of the high nickel ternary positive electrode material with surface doped cobalt element to the cobalt element in the cobalt-containing compound B in step (3) is 1:(0.002-0.02).
[0036] In some preferred embodiments of the present invention, the power of the microwave treatment in step (3) is 1000W-1800W.
[0037] In some preferred embodiments of the present invention, the temperature of the microwave treatment in step (3) is 200-400°C.
[0038] In some preferred embodiments of the present invention, the microwave treatment time in step (3) is 10 to 120 minutes.
[0039] The third aspect of the present invention provides a positive electrode sheet, wherein the active material in the positive electrode sheet is the high-nickel ternary positive electrode material in the first aspect of the present invention.
[0040] According to the third aspect of the present invention, in some embodiments of the present invention, the positive electrode sheet further includes a conductive agent and a binder.
[0041] In some preferred embodiments of the present invention, the mass ratio of the active material, the conductive agent and the binder in the positive electrode sheet is 90:5:5.
[0042] In some preferred embodiments of the present invention, the preparation method of the positive electrode sheet is: disperse the active material, conductive agent and binder in N-methylpyrrolidone, apply them on the surface of aluminum foil after stirring for 4 hours, and obtain the positive electrode sheet after vacuum drying at 120°C.
[0043] The fourth aspect of the present invention provides a lithium-ion battery assembled using the positive electrode sheet described in the third aspect of the present invention.
[0044] According to the fourth aspect of the present invention, in some embodiments of the present invention, the assembly method of the lithium-ion battery is: using the positive electrode sheet described in the third aspect of the present invention as the positive electrode of the lithium-ion battery, metallic lithium as the counter electrode of the lithium-ion battery, and assembling the button battery in a glove box filled with high-purity argon gas.
[0045] In some preferred embodiments of the present invention, the button cell is a CR2032 lithium-ion battery.
[0046] The beneficial effects of the present invention are:
[0047] 1. In the present invention, the precursor of the high-nickel ternary cathode material is coated by a spray coating method, and the formed coating layer is more uniform. After coating, it is sintered with a lithium-containing compound to prepare a high-nickel ternary cathode material with a surface doped with cobalt elements. The high-nickel ternary cathode material with a surface doped with cobalt elements is coated by a microwave heating method. The microwave heating method has the advantages of short heating time and uniform heating, which is helpful for preparing a high-nickel ternary cathode material with a uniform coating layer. The preparation method of the present invention is simple, low-cost, and environmentally friendly, and is suitable for large-scale industrial production.
[0048] 2. The cobalt element in the cobalt-doped and cobalt-coated high-nickel ternary positive electrode material prepared by the present invention is distributed at different depths, which is conducive to forming a protective layer on the surface of the positive electrode material, and can inhibit the lithium-nickel mixing phenomenon occurring in the positive electrode material during the battery cycle, so that the high-nickel ternary positive electrode material has excellent cycle performance.
[0049] 3. The cobalt element doped in the surface layer of the high-nickel ternary positive electrode material in the present invention helps to improve the cycle performance of the positive electrode material. The cobalt element coated on the surface layer of the positive electrode material can react with the residual lithium on the surface of the positive electrode material during microwave heating and coating, thereby reducing the content of residual lithium on the surface of the positive electrode material, which can effectively solve the gas production problem during the battery cycle. Under the combined effect of surface doping and surface coating of the cobalt element, the electrochemical performance of the high-nickel ternary positive electrode material in the present invention is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a SEM image of the high-nickel ternary positive electrode material prepared in Example 1 of the present invention;
[0051] Figure 2 This is the XRD diagram of the product of the mixture of cobalt hydroxide, lithium hydroxide and lithium carbonate after microwave heating;
[0052] Figure 3 The figure is a trend chart showing the capacity retention rate of lithium-ion batteries assembled with the high-nickel ternary positive electrode materials in Examples 1 to 3 and Comparative Examples 1 to 3 as a function of the number of cycles. DETAILED DESCRIPTION
[0053] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0054] Example 1 Preparation of a modified high-nickel ternary positive electrode material
[0055] (1) Preparation of a nickel-cobalt-manganese hydroxide precursor coated with cobalt element:
[0056] Take 45.82g of cobalt chloride hexahydrate and dissolve it in 120mL of deionized water to prepare a cobalt chloride aqueous solution, and place the cobalt chloride aqueous solution in a spray device. Take 1111.7g of nickel cobalt manganese hydroxide precursor Ni 0.95 Co 0.03 Mn 0.02 (OH)2 was placed in a high-efficiency mixer with a heating function and stirred at a heating temperature of 150°C and a stirring speed of 600 rpm. During the high-speed stirring of the precursor, a spray device containing a cobalt chloride aqueous solution was used for spraying. The spray time was controlled to be 30 minutes and the spray flow rate was 4 mL / min. After the solution was completely sprayed, the high-efficiency mixer with a heating function continued to stir for 120 minutes until Ni 0.95 Co 0.03 Mn 0.02 (OH)2 is fully dried to prepare a nickel-cobalt-manganese hydroxide precursor with cobalt element coated on the surface;
[0057] (2) Preparation of high nickel ternary positive electrode materials doped with cobalt element on the surface:
[0058] 1 kg of the nickel-cobalt-manganese hydroxide precursor coated with cobalt prepared in step (1) and 462 g of lithium hydroxide were placed in a ball mill for ball milling at a speed of 500 rpm for 4 h, and then calcined at 800° C. for 15 h to obtain a high-nickel ternary positive electrode material doped with cobalt on the surface;
[0059] (3) Producing a high-nickel ternary positive electrode material doped with cobalt on the surface:
[0060] 975.6 g of the high-nickel ternary positive electrode material with cobalt doped on the surface obtained in step (2) and 13.95 g of cobalt hydroxide were placed in a ball mill for ball milling, the ball milling speed was 500 rpm, the ball milling time was 4 hours, and then microwaved in a high-power microwave oven, the microwave treatment power was 1600 W, the microwave treatment temperature was 300 ° C, and the microwave treatment time was 60 minutes. The high-nickel ternary positive electrode material with cobalt doped on the surface was obtained, and the chemical formula of the high-nickel ternary positive electrode material with cobalt doped on the surface was LiNi 0.936 Co 0.044 Mn 0.02 O2·0.015LiCoO2.
[0061] Example 2 Preparation of a modified high-nickel ternary positive electrode material
[0062] (1) Preparation of a nickel-cobalt-manganese hydroxide precursor coated with cobalt element:
[0063] Take 34.92g of cobalt nitrate and dissolve it in 120mL of deionized water to prepare a cobalt nitrate aqueous solution, and place the cobalt nitrate aqueous solution in a spray device. Take 1111.7g of nickel cobalt manganese hydroxide precursor Ni 0.95 Co 0.03 Mn 0.02 (OH)2 was placed in a high-efficiency mixer with a heating function for stirring, the heating temperature was 150°C, and the stirring speed was 600rpm. During the high-speed stirring of the precursor, a spray device containing a cobalt nitrate aqueous solution was used for spraying, the spray time was controlled to be 30min, the spray flow rate was 4mL / min, and the solution was completely sprayed. After the spraying was completed, the high-efficiency mixer with a heating function continued to stir for 120min until the precursor was fully dried, and a nickel-cobalt-manganese hydroxide precursor with a cobalt element coated on the surface was prepared;
[0064] (2) Preparation of high nickel ternary positive electrode materials doped with cobalt element on the surface:
[0065] 1 kg of the nickel-cobalt-manganese hydroxide precursor coated with cobalt obtained in step (1) and 462 g of lithium hydroxide were placed in a ball mill for ball milling at a speed of 500 rpm for 4 h, and then calcined at 800° C. for 15 h to obtain a high-nickel ternary positive electrode material doped with cobalt on the surface;
[0066] (3) Producing a high-nickel ternary positive electrode material doped with cobalt on the surface:
[0067] 975.6 g of the high-nickel ternary positive electrode material with cobalt doped on the surface obtained in step (2) and 9.30 g of cobalt hydroxide were placed in a ball mill for ball milling, the ball milling speed was 500 rpm, the ball milling time was 4 hours, and then microwave heating was performed in a high-power microwave oven, the microwave heating power was 1600 W, the microwave heating temperature was 300 ° C, and the microwave heating time was 60 minutes. The high-nickel ternary positive electrode material with cobalt doped on the surface was obtained, and the chemical formula of the high-nickel ternary positive electrode material with cobalt doped on the surface was LiNi 0.94 Co 0.04 Mn 0.02 O2·0.01LiCoO2.
[0068] Example 3 Preparation of a modified high-nickel ternary positive electrode material
[0069] (1) Preparation of a nickel-cobalt-manganese hydroxide precursor coated with cobalt element:
[0070] Take 84.65g of cobalt acetate tetrahydrate and dissolve it in 120mL of deionized water to prepare a cobalt acetate aqueous solution, and place the cobalt acetate aqueous solution in a spray device. Take 1kg of nickel cobalt manganese hydroxide precursor Ni 0.95 Co 0.03 Mn0.02 (OH)2 was placed in a high-efficiency mixer with a heating function for stirring, the heating temperature was 150°C, and the stirring speed was 600rpm. During the high-speed stirring of the precursor, a spray device containing an aqueous solution of cobalt acetate was used for spraying, the spray time was controlled to be 30min, the spray flow rate was 4mL / min, and the solution was completely sprayed. After the spraying was completed, the high-efficiency mixer with a heating function continued to stir for 120min until the precursor was fully dried, and a nickel-cobalt-manganese hydroxide precursor with a cobalt element coated on the surface was prepared;
[0071] (2) Preparation of high nickel ternary positive electrode materials doped with cobalt elements:
[0072] 1 kg of the surface-coated cobalt-containing nickel-cobalt-manganese hydroxide precursor prepared in step (1) was mixed with 462 g of lithium hydroxide by ball milling at a speed of 500 rpm for 4 h, and then calcined at 800° C. for 15 h to obtain a high-nickel ternary positive electrode material doped with cobalt on the surface;
[0073] (3) Producing a high-nickel ternary positive electrode material doped with cobalt on the surface:
[0074] 1 kg of the high-nickel ternary positive electrode material doped with cobalt prepared in step (2) was mixed with 4.65 g of cobalt hydroxide by ball milling at a speed of 500 rpm for 4 h, and then heated in a high-power microwave oven at a power of 1600 W, a temperature of 300° C., and a time of 60 min. The high-nickel ternary positive electrode material doped with cobalt was obtained. The chemical formula of the high-nickel ternary positive electrode material doped with cobalt is LiNi 0.945 Co 0.035 Mn 0.02 O2·0.005LiCoO2.
[0075] Comparative Example 1
[0076] Comparative Example 1 is different from Example 1 in that the high-nickel ternary positive electrode material prepared in Comparative Example 1 is neither coated with cobalt element nor doped with cobalt element. The specific steps are as follows:
[0077] Take 1kg of nickel-cobalt-manganese hydroxide precursor Ni 0.95 Co 0.03 Mn 0.02 (OH)2 was mixed with 462g lithium hydroxide by ball milling at a speed of 500rpm for 4h, and then calcined at 800℃ for 15h to obtain the high nickel ternary positive electrode material LiNi 0.95 Co 0.03 Mn 0.02 O2.
[0078] Comparative Example 2
[0079] Comparative Example 2 is different from Example 1 in that the high-nickel ternary positive electrode material prepared in Comparative Example 2 is only coated with cobalt element without doping with cobalt element. The specific steps are as follows:
[0080] (1) Take 1 kg of nickel-cobalt-manganese hydroxide precursor Ni 0.95 Co 0.03 Mn 0.02 (OH)2 was mixed with 462 g of lithium hydroxide by ball milling at a speed of 500 rpm for 4 h, and then calcined at 800 °C for 15 h to obtain a high-nickel ternary positive electrode material.
[0081] (2) 975.6 g of the high-nickel ternary positive electrode material obtained in step (1) was mixed with 13.95 g of cobalt hydroxide by ball milling at a speed of 500 rpm for 4 h, and then heated in a high-power microwave oven at a power of 1600 W, a temperature of 300 ° C, and a time of 60 min. The high-nickel ternary positive electrode material LiNi coated with cobalt element was obtained. 0.95 Co 0.03 Mn 0.02 O2.
[0082] Comparative Example 3
[0083] The difference between Comparative Example 3 and Example 1 is that the high-nickel ternary positive electrode material prepared in Comparative Example 3 is only a high-nickel ternary positive electrode material doped with cobalt element, and no cobalt coating is performed. The steps are as follows:
[0084] (1) Take 45.82g of cobalt chloride hexahydrate and dissolve it in 120mL of deionized water to prepare a cobalt chloride aqueous solution, and place the cobalt chloride aqueous solution in a spray device. Take 1111.7g of nickel cobalt manganese hydroxide precursor Ni 0.95 Co 0.03 Mn 0.02 (OH)2 was placed in a high-efficiency mixer with a heating function for stirring, the heating temperature was 150°C, and the stirring speed was 600rpm. During the high-speed stirring of the precursor, a spray device equipped with a cobalt chloride aqueous solution was used for spraying, the spray time was controlled to be 30min, the spray flow rate was 4mL / min, and the solution was completely sprayed. After the spraying was completed, the high-efficiency mixer with a heating function continued to stir for 120min until the precursor was fully dried to obtain a nickel-cobalt-manganese hydroxide precursor with a cobalt element coated on the surface;
[0085] (2) 1 kg of the surface-coated cobalt-containing nickel-cobalt-manganese hydroxide precursor prepared in step (1) was mixed with 462 g of lithium hydroxide by ball milling at a speed of 500 rpm for 4 h, and then calcined at 800 ° C for 15 h to obtain a high-nickel ternary positive electrode material doped with cobalt on the surface. The chemical formula of the high-nickel ternary positive electrode material doped with cobalt on the surface is LiNi 0.936 Co 0.044 Mn 0.02 O2·0.015LiCoO2.
[0086] Characterization and performance testing of modified high nickel ternary cathode materials
[0087] (1) Morphological characterization:
[0088] Figure 1 The SEM image of the modified high-nickel ternary positive electrode material prepared in Example 1 shows that the particle surface of the modified high-nickel ternary positive electrode material has a fine powder distribution (such as Figure 1 The circled part in the middle), which is the substance formed by the reaction of cobalt hydroxide with the residual lithium on the surface of the modified high-nickel ternary positive electrode material under microwave heating conditions.
[0089] (2) Test of residual lithium content in high nickel ternary positive electrode materials:
[0090] The test method for the residual lithium content in the high-nickel ternary positive electrode material is as follows: the high-nickel ternary positive electrode material is dispersed in deionized water, stirred for 30 minutes, filtered with a vacuum filtration device, the filtrate is collected and weighed, the filtrate is placed in a potentiometric titrator, and a 0.1 mol / L hydrochloric acid labeled solution is used for potentiometric titration to pH ≤ 4, and the consumption volume of hydrochloric acid at the mutation point in the titration curve is recorded. Then the data is processed according to the conventional method in the art to calculate the residual lithium content in the high-nickel ternary positive electrode material.
[0091] The test results of the residual lithium content in the high-nickel ternary positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1. It can be seen from the data in Table 1 that the residual lithium content in Examples 1 to 3 is lower than that in Comparative Examples 1 to 3. This is because when the cobalt element is microwave-coated, cobalt hydroxide reacts with the residual lithium on the surface of the material (the residual lithium is composed of lithium hydroxide and lithium carbonate) to generate lithium cobaltate, thereby reducing the residual lithium content on the surface of the material. Figure 2 The XRD spectrum of the product of the mixture of cobalt hydroxide, lithium hydroxide and lithium carbonate after microwave heating, wherein the molar ratio of cobalt hydroxide, lithium hydroxide and lithium carbonate is 2:1:1. Figure 2It can be seen that the peaks in the XRD spectrum are all characteristic peaks of LiCoO2, which further illustrates that during the microwave heating process of the modified high-nickel ternary positive electrode material prepared in the embodiment of the present invention, cobalt hydroxide reacts with residual lithium composed of lithium hydroxide and lithium carbonate to generate LiCoO2.
[0092] Table 1 Statistics of residual lithium content in high nickel ternary positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3
[0093] sample Residual lithium content (%) Example 1 0.1782 Example 2 0.1945 Example 3 0.2069 Comparative Example 1 0.2744 Comparative Example 2 0.2146 Comparative Example 3 0.2698
[0094] (3) Electrochemical performance test
[0095] Assembly of lithium-ion battery: The conductive agent and the binder are mixed in a certain proportion and added to 1-methyl 2-pyrrolidone. After being fully stirred in a vacuum mixer, the positive electrode material in the embodiment of the present invention or the comparative example is added (wherein the mass ratio of the positive electrode material, the binder and the conductive agent is 90:5:5). The solid content of the slurry is 50%. After being fully stirred, a slurry of electrode material is prepared. The slurry is coated on aluminum foil, and the positive electrode sheet is obtained by drying and rolling. In this embodiment, the surface density of the positive electrode sheet is 3.7 g / cm 2 The obtained positive electrode sheet was used as the positive electrode and metal lithium was used as the counter electrode to assemble a CR2032 type lithium ion button cell for the test of electrochemical performance. The electrolyte was E20 purchased from Shenzhen Xinzhoubang Technology Co., Ltd.
[0096] Electrochemical performance test of lithium-ion batteries: The test equipment is the Blue Electric Battery Test System, the voltage window is 2.8V-4.3V, the current density is 1C, and the test temperature is room temperature.
[0097] Figure 3 The capacity retention rate of lithium ion batteries assembled using the positive electrode materials in Examples 1 to 3 and Comparative Examples 1 to 3 varies with the number of cycles. Figure 3 It can be seen from the data that, compared with Comparative Examples 1 to 3, the capacity retention rate of the lithium-ion batteries assembled using the positive electrode materials in Examples 1 to 3 decreases more slowly with the number of cycles, and has a higher capacity retention rate. This shows that the simultaneous cobalt doping and cobalt coating of the high-nickel ternary positive electrode material can further improve the cycle performance of the high-nickel ternary positive electrode material, and the electrochemical performance is better than that of the lithium-ion battery assembled with the positive electrode material simply doped with cobalt or coated with cobalt. In addition, the rate at which the capacity retention rate of the lithium-ion batteries assembled with the positive electrode materials of Comparative Examples 2 and 3 decreases is slower than that of the lithium-ion battery assembled with the positive electrode material in Comparative 1, indicating that a single cobalt coating or cobalt doping of the high-nickel ternary positive electrode material can improve the cycle performance of the high-nickel ternary positive electrode material.
[0098] Table 2 shows the electrochemical properties of lithium-ion batteries assembled with high-nickel ternary positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, and Table 2 includes the first-week discharge specific capacity, first-week efficiency, and 100-cycle capacity retention rate. As can be seen from Table 2, the first-week discharge specific capacity and first-week efficiency of the lithium-ion batteries prepared with the high-nickel ternary positive electrode materials in Examples 1 to 3 are higher than those of the lithium-ion batteries assembled with the high-nickel ternary positive electrode materials in Comparative Examples 1 to 3, and the capacity retention rate of the lithium-ion batteries assembled with the high-nickel ternary positive electrode materials in Examples 1 to 3 for 100 cycles is significantly higher than that of the lithium-ion batteries assembled with the high-nickel ternary positive electrode materials in Comparative Examples 1 to 3, which indicates that the use of the method in the embodiment of the present invention to dope and coat the high-nickel ternary positive electrode materials with cobalt elements can significantly improve the cycle performance and cycle life of the high-nickel ternary positive electrode materials.
[0099] Table 2 Electrochemical properties of high nickel ternary positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3
[0100] sample First week discharge capacity (mAh / g) First week efficiency (%) 100 cycles capacity retention rate (%) Example 1 229.8 92.7 83.74 Example 2 228.9 92.0 81.53 Example 3 227.3 92.1 80.31 Comparative Example 1 226.8 90.9 69.38 Comparative Example 2 226.7 91.7 78.55 Comparative Example 3 226.9 91.0 74.55
[0101] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high-nickel ternary positive electrode material, characterized in that: The ternary positive electrode material is a high-nickel ternary positive electrode material doped with cobalt and coated with cobalt, wherein the mass fraction of the cobalt doping is 0.2-2%, and the thickness of the coating layer coated with cobalt is 20-200 nm; The preparation method of the high-nickel ternary positive electrode material comprises the following steps: (1) Cobalt-containing compound A is coated on nickel-cobalt-manganese hydroxide precursor Ni x Co y Mn 1-x-y (OH)2, preparing a nickel-cobalt-manganese hydroxide precursor coated with cobalt, wherein 1.00>x≥0.6, y>0, 1-xy>0; (2) mixing the nickel-cobalt-manganese hydroxide precursor coated with cobalt described in step (1) with a lithium-containing compound and calcining the mixture to prepare a high-nickel ternary positive electrode material doped with cobalt on the surface; (3) The high-nickel ternary positive electrode material doped with cobalt element described in step (2) is mixed with the cobalt-containing compound B and subjected to microwave treatment to prepare a high-nickel ternary positive electrode material LiNi x Mn y Co 1-x-y O2·nLiCoO2, where 1.00>x≥0.6, y>0, 1-xy>0, n>0; Wherein, the calcination temperature in step (2) is 700-1000° C., and the calcination time is 10-20 hours.
2. The method for preparing the high-nickel ternary positive electrode material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Cobalt-containing compound A is coated on nickel-cobalt-manganese hydroxide precursor Ni x Co y Mn 1-x-y (OH)2, preparing a nickel-cobalt-manganese hydroxide precursor coated with cobalt, wherein 1.00>x≥0.6, y>0, 1-xy>0; (2) mixing the nickel-cobalt-manganese hydroxide precursor coated with cobalt described in step (1) with a lithium-containing compound and calcining the mixture to prepare a high-nickel ternary positive electrode material doped with cobalt on the surface; (3) The high-nickel ternary positive electrode material doped with cobalt element described in step (2) is mixed with the cobalt-containing compound B and subjected to microwave treatment to prepare a high-nickel ternary positive electrode material LiNi x Mn y Co 1-x-y O2·nLiCoO2, where 1.00>x≥0.6, y>0, 1-xy>0, n>0; Wherein, the calcination temperature in step (2) is 700-1000° C., and the calcination time is 10-20 hours.
3. The method according to claim 2, characterized in that In step (1), a solution obtained by mixing the cobalt-containing compound A with water is coated on the Ni x Co y Mn 1-x-y (OH)2 surface, wherein the spraying time of the spraying method is 5 to 120 minutes, and the spraying flow rate is 3 to 6 mL / min.
4. The method according to claim 3, characterized in that The mass ratio of the cobalt-containing compound A to water is 1:(1-100).
5. The method according to claim 2, characterized in that: The cobalt-containing compound A in step (1) comprises at least one of cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, and cobalt sulfate heptahydrate. x Co y Mn 1-x-y The molar ratio of (OH)2 to the cobalt element in the cobalt-containing compound A is 1:(0.002-0.02).
6. The method according to claim 2, characterized in that The lithium-containing compound in step (2) includes at least one of lithium hydroxide, lithium carbonate, lithium fluoride, lithium chloride, and lithium nitrate. x Co y Mn 1-x-y The molar ratio of (OH)2 to the lithium element in the lithium-containing compound is 1:(1-1.2).
7. The method according to claim 2, characterized in that: The cobalt-containing compound B in step (3) includes at least one of cobalt oxide, cobalt tetroxide, cobalt oxyhydroxide, cobalt hydroxide, cobalt trioxide, cobalt carbonate, cobalt acetate, and cobalt oxalate. The molar ratio of the high-nickel ternary positive electrode material with cobalt element doped on the surface in step (3) to the cobalt element in the cobalt-containing compound B is 1:(0.002-0.02).
8. The method according to claim 2, characterized in that: The time of the microwave treatment in step (3) is 10 to 120 minutes; the temperature of the microwave treatment is 200 to 400° C.; and the power of the microwave treatment is 1000 to 1800W.
9. A positive electrode sheet prepared using the high-nickel ternary positive electrode material described in claim 1, wherein the positive electrode sheet further comprises a conductive agent and a binder.
10. A lithium ion battery assembled using the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
High-nickel cathode material and preparation method thereof and lithium-ion battery
CN105185962A
High-nickel ternary material with cobalt-rich surface layer and preparation method and application thereof
CN106898751A
Lithium cobaltate-coated high-nickel ternary positive electrode material and preparation method thereof
CN110247031A
Ternary positive electrode material, preparation method thereof and lithium ion battery
CN111200120A
Positive electrode material, preparation method thereof and lithium ion battery
CN112750999A